Interference of irrelevant information in multisensory selection depends on attentional set - Jensen, A; Merz, S; Spence, C; Frings, CH (Springer US, 2019)
In the multisensory world in which we live, certain objects and events are of more relevance than others. In the laboratory, this broadly equates to the distinction between targets and distractors. In selection situations like the flanker task, the evidence suggests that the processing of multisensory distractors is influenced by attention. Here, multisensory distractor processing was investigated by modulating attentional set in three experiments in a flanker interference task, in which the targets were unisensory while the distractors were multisensory. Attentional set was modulated by making the target modality either predictable or unpredictable (Experiments 1 vs. 2, respectively). In Experiment 3, this manipulation was implemented on a within-experiment basis. Furthermore, the third experiment compared audiovisual distractors (used in all experiments) with distractors with one feature in a neutral modality (i.e., touch), that never appeared as the target modality in the flanker task. The results demonstrate that there was no interference from the response-compatible crossmodal distractor feature when the target modality was predictable (i.e., blocked). However, when the modality was varied on a trial-by-trial basis, this crossmodal feature significantly influenced information processing. By contrast, a multisensory distractor with a neutral crossmodal feature never influenced behavior. This finding suggests that the processing of multisensory distractors depends on attentional set. When the target modality varies randomly, participants include features from both modalities in their attentional set and the irrelevant crossmodal feature, now part of the set, influences information processing. In contrast, interference from the crossmodal distractor feature does not occur when it is not part of the attentional set.